Using VAM in high-stakes employment decisions - Paige, Mark (Phi Delta Kappan, 2012)
Value-added models (VAMs) are becoming an important tool in improving teacher evaluation. VAMs' premise is that they can statistically isolate a teacher's effect on a student's test score. In other words, we can attribute a student's growth to a particular teacher, and VAMs' proponents contend that they should be used to make a host of personnel decisions, including termination. But this has come under serious debate. Because VAMs are subject to some reliability infirmities, many question their use in making high stakes employment decisions, such as termination. The literature has yet to address VAMs at the intersection of the law, which is striking, given the legal implications associated with teacher termination.